185k views
5 votes
Find the difference of functions s and r shown below. r(x) = –x² + 3x s(x) = 2x + 1 (s – r)(x) =

User TapanHP
by
5.5k points

2 Answers

4 votes

Answer:


(s-r)(x)=x^2-x+1

Explanation:

  • So we subtract functions the same way we do numbers, ergo

  • (s-r)(x)=s(x)-r(x)\\ (2x+1)-(-x^2+3x)\\2x+1+x^2-3x\\x^2+2x-3x+1\\(s-r)(x)=x^2-x+1
User Gori
by
5.8k points
7 votes

Answer:

There are 2 parts of the equation

The first answer to answer is (2x+1)--(-x2+3x)

The second answer is x2--x+1

Explanation:

I hope you have a wonderful day!!

Love you all!!

User Mattia
by
6.0k points